Radar Observation of Extreme Vertical Drafts in the Polar Summer Mesosphere - J. L. Chau; R. Marino; F. Feraco; J. M. Urco; G. Baumgarten; F.‐J. Lübken; W. K. Hocking; C. Schult; T. Renkwitz; R. Latteck (Geophysical Research Letters)
Abstract The polar summer mesosphere is the Earth's coldest region, allowing the formation of mesospheric ice clouds. These ice clouds produce strong polar mesospheric summer echoes (PMSE) that are used as tracers of mesospheric dynamics. Here, we report the first observations of extreme vertical drafts (±50 ms−1) in the mesosphere obtained from PMSE, characterized by velocities more than five standard deviations larger than the observed vertical wind variability. Using aperture synthesis radar imaging, the observed PMSE morphology resembles a solitary wave in a varicose mode, narrow along propagation (3–4 km) and elongated (>10 km) transverse to propagation direction, with a relatively large vertical extent (∼13 km). These spatial features are similar to previously observed mesospheric bores, but we observe only one crest with much larger vertical extent and higher vertical velocities.